Evolução cromossômica e diversidade genética em espécies de peixes da família Arapaimidae (Teleostei: Osteoglossiformes) - Oliveira, Ezequiel Aguiar de (Universidade Federal de São Carlos, 2019)
The Neotropical region exhibits the largest diversity of freshwater fishes in the world and the demographic history of several taxa is related to the geomorphological and climatic history of this region. Among the Osteoglossiformes, the Arapaimidae family is represented by only two genera, with a South American representative Arapaima and another African Heterotis, an important ichthyological group that still has lacked genetic and cytogenetic studies. Therefore, the present work with the use of advanced population genomics tools, selection of demographic models by machine learning, conventional and molecular cytogenetics analysis, aimed at developing a broad understanding of the chromosomal, molecular and phylogeographic diversity of these species. We aimed to better clarify the evolutionary events that shaped the demographic history of this fish group. For that, South American and African representatives of Arapaimidae, namely Arapaima (four natural populations of the Am basin, three of the To-Ar basin and three fish farms) and Heterotis niloticus (a population of the Oluwa River in Nigeria) were examined. The species differed significantly by means of diploid chromosome numbers, with 2n = 56 found in Arapaima and 2n = 40 exhibited by H. niloticus. However, these species presented some general tendencies shared by other Osteoglossiformes analyzed so far, regarding the presence of only one pair of chromosomes bearing 18S and 5S rDNA sites and karyotypes dominated by acrocentric-submetacentric chromosomes, thus corresponding to hypothetical karyotype patterns ancestral to teleosts. In addition, their genomes showed remarkable divergence in terms of repetitive DNA content and distribution as revealed by Comparative Genomic Hybridization (CGH). On the other hand, genomic diversity of single-copy sequences (SNPs), retrieved through principal component analysis (PCA), based on alleles obtained by the DArTseq procedure, demonstrated a very low genetic distance between these genera. These data provided a clear view of the genetic diversity between African and South American Arapaimidae species and were highly consistent with the chromosomal, geographic and historical data, helping to understand its evolutionary diversification. Concerning the investigations of the genus Arapaima in South America, we observed a higher general level of genetic diversity in the Am populations when compared to the one observed in the To-Ar basin. In addition, a high genetic differentiation between the populations of the different basins was observed. By including samples of fish farming, the most likely ancestry of the used breeding herds was revealed, raising concerns about the use of broodstocks outside the distribution of their genetic grouping. No significant chromosome differentiations in the karyotypic structure and repetitive DNA compositions among the studied Arapaima populations was observed. Although the main routes for Arapaima colonization in South America are still unclear, the model selection from convolutional neural networks (CNN) applied to our empirical data indicated a scenario in which the Am basin was the first to be colonized, followed by the To-Ar one. Other studies should focus on a wider historical biogeographic reconstruction of the order Osteoglossiformes, which may potentially explain its relationship with the Gondwana break-up and the presence of this taxon in South America.
Chromosomal evolution and genetic diversity in fish species of Arapaimidae family (Teleostei: Osteoglossiformes)
Evolución cromosómica y diversidad genética en especies de Pez de la familia Arapaimidae (Teleostei: Osteoglossiformes)
Keywords: Cromossomos; SNPs; Gondwana; DNAs repetitivos; Peixes; Citogenética molecular; Chromosomes; Fishes; Repetitive DNAs; Molecular cytogenetics; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL